Integration of the Montessori Approach in Inclusive Education as an Effort to Achieve Social Sustainability: A Study at SIT Al Uswah Pamekasan - Nurul Qomariyah; Siti Azizah (IAIN Madura, 2026)
This study aims to analyze the integration of the Montessori approach into inclusive education practices as a strategy to achieve social sustainability at SIT Al Uswah Pamekasan. Amid increasing issues of intolerance, the marginalization of children with special needs, and a growing empathy crisis in primary education, schools are required to develop a learning ecosystem that is equitable, participatory, and sustainable. The Montessori approach, developed by Maria Montessori, emphasizes child-centered learning, respect for diversity, and the development of independence and social responsibility. This study employs a qualitative approach with a descriptive design to explore the practice of integrating Montessori pedagogy within an inclusive setting, including learning strategies, school culture, and the dynamics of students’ social interactions. Data were collected through observation, in-depth interviews, and document analysis, and were analyzed thematically. The findings indicate that the integration of Montessori principles into inclusive education contributes to strengthening social cohesion, enhancing students’ empathy, and fostering a supportive and non-discriminatory learning environment. These findings suggest that the synergy between Montessori pedagogy and inclusive education can serve as a strategic model for fostering social sustainability at the primary education level.